Influence of landscape on the presence of Batrachochytrium dendrobatidis and Ranavirus in tadpoles in the southern Atlantic Forest of Brazil - Santos, Roseli Coelho dos; Dalmolin, Diego Anderson; Ruggeri, Joice; Brum, Diego; Veronez, Mauricio Roberto; Lucas, Elaine Maria; Tozetti, Alexandro Marques (Frontiers in Amphibian and Reptile Science, 2024)
Introduction Habitat loss, as well as infectious diseases, have been suggested as the main causes for the worldwide decline of amphibian populations. Thus, the search for biotic indicators is a useful tool for mapping priority demands in disease management. Aims Here we analyzed the prevalence of two pathogens, Batrachochytrium dendrobatidis (Bd) and Ranavirus (Rv), in anuran communities in southern Brazil. We explored the relationship between the prevalence of Bd and landscape class and used an indicator-species and indicator-community approach to identify which species and communities have the potential to indicate the presence of Bd. Methods We used histological analyses to access Bd and PCR for Rv in tadpole communities. Key results Our data, based on 26 anuran communities, revealed high Bd prevalence but absence of Rv. Three species, of the 26 communities studied, were found to be Bd indicators, including endemic species from southern Brazil and Argentina. Additionally, the analysis with an indicator-community approach revealed that communities from larger forest areas are Bd indicators. Conclusions Analyses at the community level, which relate landscape to pathogens, provide unprecedented and highly relevant information for fragmented Atlantic Forest landscapes. Based on our results, we argue that even communities in larger forest patches (apparently well-preserved) are susceptible to Bd and deserve attention regarding the possibility of incidence of chytridiomycosis. Implications. From our results, we consider that the use of Bd-indicator species and Bd-indicator communities is a useful approach for conservation and could be used to evaluate the threatened status of species and for proposals for landscape management.